TIMING OF HOG COLERA VACCINATION BY MEASURING MATERNAL ANTIBODY TITERS - Suardana, Ida Bagus Kade; Widyastuti, Sri Kayati; Pradnyadana, Ida Bagus Krisna; Agustina, Kadek Karang (Buletin Veteriner Udayana, 2022)
Pigs are livestock that have relatively rapid growth and development, as a source of animal protein has a high economic value. However, raising pigs is often infected with the Hog cholera virus. Hog Cholera is characterized by sudden death with high morbidity and mortality. Disease control through vaccination has been carried out, but cases of disease still occur. The success of vaccination can be influenced by various factors, including: the vaccine factor, the implementer, and the animal factor. This study aims to determine the maternal antibody titer of piglets from sows who have been vaccinated against hog cholera. The study used 10 samples of piglets from sows that had been vaccinated. Serum samples were taken on days 7, 14, and 21. Antibody titers were checked using ELISA. The data obtained were analyzed using analysis of variance. The results showed that there was a significant decrease in maternal antibody titers (p<0.05) on the 14 th and 21 st days compared to the 7 th day. There is a significant relationship (p<0.05) between age (days) and the value of optical density (OD) of maternal antibodies, the correlation coefficient is 0.852, with the equation Y=1.195e -0.021X . The conclusion is that the older the piglets are, the lower the OD value will be, but the longer the decline is, the smaller the decrease. At the age of 42 days, the maternal antibody OD value will reach 0.50, so it is feasible to be vaccinated.